Resilience Of The Perang Obor Tradition In The Midst Of The Covid-19 Pandemic - Kurniawan, Muhammad Andi; Wijayanti, Tutik (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2022)
The purpose of this study was to examine what adaptations or adjustments were made to the implementation of the Perang Obor tradition in the midst of the COVID-19 pandemic and the response from the people of Tegalsambi Village. The method used in this research was a qualitative approach with interview and observation techniques. Interviews were conducted with the community and the village head of Tegalsambi. While the observations were carried out by seeing directly what the Perang Obor was like in the midst of the COVID-19 pandemic. The results of the study found the fact that the existence of the Perang Obor tradition in the midst of the covid-19 pandemic was maintained but with some changes. The changes include the implementation of health protocols, the number of participants and limited time to avoid crowds that can become a medium for the spread of COVID-19. This study also found the fact that the policy of the village head continued to carry out the Perang Obor tradition in the midst of a pandemic because this tradition is related to meaningful cultural values and ideologies. Therefore, if it is abolished, it is feared that it will cause conflict for the people of Tegalsambi because the response from the people of Tegalsari has been very positive although they hope that the Perang Obor tradition can be carried out as vibrantly as when there was no COVID-19 pandemic.